Effect of long term chilled (up to 5 weeks) then frozen (up to 12 months) storage at two different sub-zero holding temperatures on beef: 2. Lipid oxidation and fatty acid profiles. (February 2018) - Holman, Benjamin W.B.; Coombs, Cassius E.O.; Morris, Stephen; Bailes, Kristy; Hopkins, David L.
Abstract: Lipid oxidation and fatty acid (FA) profiles were evaluated for beef M. longissimus lumborum (LL) stored under different chilled-then-frozen storage combinations (up to 5 and 52 weeks, respectively) and two frozen holding temperatures (− 12 °C and − 18 °C). FA profile variation was observed, with increasing frozen storage periods resulting in unsaturated FA levels declining as saturated FA levels increased. Polyunsaturated and health claimable FA levels also tended to decline with increasing chilled storage period, albeit insignificant within the constraints of the experimental design. Peroxidase activity, TBARS and oxidation-reduction potential analyses reflected these FA changes. These, when compared against existing consumer thresholds, suggest a perceptible detraction from LL held under long-term frozen storage durations that are less evident earlier as dependent on the preceding chilled storage period. Negligible impact of frozen storage holding temperatures was observed on measured traits. These results suggest long-term chilled-then-frozen storage can influence beef lipid stability, healthy FA profile and therefore the healthiness of beef.